Larval morphology and DNA barcoding of the marine Tanytarsini genus Yaetanytarsus Sasa, 1990 (Diptera: Chironomidae) - Kodama, Atsuya; Saito, Hidetoshi; Kawai, Koichiro (Zootaxa, 2026)
The marine Tanytarsini genus Yaetanytarsus Sasa, 1990 has been distinguished from Pontomyia Edwards, 1926 by the number of posterior parapod claws and the tapered form of abdominal segment VIII in the larval morphology. To evaluate these diagnostic characteristics, we identified the larvae of the three Yaetanytarsus species using mitochondrial cytochrome c oxidase subunit I (COI) DNA barcoding and subsequently examined their morphology. In total, 13 larvae and eight adults were analyzed. Larval sequences clustered unambiguously with conspecific adults, showing intraspecific K2P distances of 0.0–1.7% and interspecific distances exceeding 10%. The larvae of the three species (Y. boodleae (Tokunaga, 1933), Y. iriomeneus (Sasa & Suzuki, 2000), and Y. lamnicaudus (Tokunaga, 1964)) were examined and exhibited similar morphologies. Morphological comparison revealed that Y. lamnicaudus (Tokunaga, 1964) has 39–61 posterior parapod claws, which overlaps with the range in Pontomyia and indicates this characteristic is not uniformly reliable for separating these genera. Here, we provide the first detailed larval descriptions of these three species of Yaetanytarsus and demonstrate that COI barcoding is a robust tool for species identification in maritime Tanytarsini.